An outbreak of multiply antibiotic-resistant ST49:ST128:KL11:OCL8 Acinetobacter baumannii isolates at a Sydney hospital. (16th January 2021) - Hamidian, Mohammad; Ambrose, Stephanie J; Blackwell, Grace A; Nigro, Steven J; Hall, Ruth M
Abstract: Objectives: To understand the acquisition of resistance genes by a non-GC1, non-GC2 Acinetobacter baumannii strain responsible for a 4 year outbreak at a Sydney hospital. Methods: Representative isolates were screened for resistance to antibiotics. Three were subjected to WGS using Illumina HiSeq. One genome was completed with MinION long reads. Resistance regions were compared with known sequences using bioinformatics. Results: Isolates were resistant to third-generation cephalosporins, gentamicin and tobramycin, sulfamethoxazole and erythromycin. Sequenced isolates were ST49 (Institut Pasteur scheme) and ST128 (Oxford scheme) and carried KL11 at the capsule locus and OCL8 at the lipooligosaccharide outer core locus. The complete genome of isolate J9 revealed that the resistance genes were all in plasmids; pRAY* contained aadB, and a large plasmid, pJ9-3, contained sul2 and floR genes and a dif module containing the mph (E)- msr (E) macrolide resistance genes. Transposon Tn 6168, consisting of a second copy of the chromosomal ampC gene region flanked by ISAba1s, confers resistance to third-generation cephalosporins. Tn 6168 is located inside the mph (E)- msr (E) dif module. pJ9-3 includes a set of four dif modules and the orientation of the p dif sites, XerC-XerD or XerD-XerC, alternates. A large transposon, Tn 6175, containing tniCABDE transposition genes and genes annotated as being involved in heavy metal metabolism, uptake or export was found in the comM gene. Other ST49:ST128:KL11:OCL8 genomes found in the GenBank WGS database carried Tn 6175 but neither of the plasmids carrying the resistance genes. Conclusions: An early carbapenem-susceptible A. baumannii outbreak recorded in Australia was caused by an unusual clone that had acquired plasmids carrying antibiotic resistance genes.